Enhancement on the tribological properties of poly(phthalazinone ether sulfone ketone) by carbon nanotube‐supported graphitic carbon nitride hybrid. Issue 9 (15th June 2020) - Zhang, Mengjie; Chen, Beibei; Dong, Zhe; Wang, Shuang; Li, Xiang; Jia, Yuhan; Yan, Fengyuan
Abstract: A novel hybrid of carbon nanotube‐supported graphitic carbon nitride (g‐C3 N4 /CNT) was firstly fabricated via facile calcination method, and then filled into poly (phthalazinone ether sulfone ketone) (PPESK) to prepare self‐lubricating composite film. The microstructure and chemical composition of g‐C3 N4 /CNT hybrid were characterized, and its enhancement on the tribological properties of PPESK was investigated by comparing to pure PPESK and its composite films with g‐C3 N4 or CNT only. Results showed that g‐C3 N4 was in situ attached to CNT surface uniformly, which favored for improving the physical and chemical interfacial interaction between fillers and PPESK. Besides, by the incorporation of g‐C3 N4 /CNT, the hardness and elastic modulus of PPESK were improved by 15.05% and 41.75%, respectively. More importantly, PPESK‐g‐C3 N4 /CNT composite film showed the best tribological property among PPESK composite films. Its friction coefficient and wear rates were 65.5% and 84.1% lower than those of pure PPESK, as a result of good dispersion and interfacial action, as well as synergism between CNT and g‐C3 N4 . Based on the worn surface analysis, the enhancement mechanism of g‐C3 N4 /CNT was proposed. Abstract :